Derivative Zero - Crossing Spectrophotometry Of Binary Mixtures Of Acetyl Acetonates Of Micro – Amounts Of Mn (Ii) And Al (Iii). - Baghdad Science Journal (مجلة بغداد للعلوم)
New derivative molecular absorption spectrophotometric methods have been developed for the determination of Al (III) , Mn (II) , individually and binary mixtures . The aim of this model of study is to obtain analytical results characterized by adequate standard of analytical figures of merits through application of derivative Spectrophotometry (dnA/d?n). The two metals acetyl acetonates are chemically stable and are widely used as catalysts . Where Interferences are probable due to very close or nearby peaks or Summits, the Zero – Crossing derivative measurement technique is used to avoid interfering effects between two metals pairs.